BILBERRY (VACCINIUM MYRTILLUS) AND ELDERBERRY FRUIT (SAMBUCUS NIGRA L.) FROM ROMANIA PROCESSED AS CONFITURE. EVOLUTION OF COLOR, TOTAL CONTENT OF ANTHOCYANIN AND VITAMIN C - MARIA LIDIA IANCU; VALENTINA MĂDĂLINA MOGA; MIHAELA ADRIANA TIȚA; OVIDIU TIȚA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The subject of the present paper is the influence of sugar preservation and heat treatment on the total content of anthocyanins, vitamin C, and the color of the confiture. In Romania, bilberry confiture is in demand while that made from wild black elderberry is almost non-existent for most people. Thus, a comparative analysis of the two varieties of confiture has been carried out taking into consideration the similarity of the macroscopic characteristics of the raw materials, namely the forest fruits. Thus, it has been established that the vitamin C content decreased by 81 % in the bilberry confiture (BC) and by 52 % in that of wild elderberry, as compared to the vitamin content in the fruit. The total content of anthocyanins decreases by 45 % in the BC sample and by 25 % in the elderberry confiture (EC). The values of the color parameters showed a trend towards dark brownish-red with a distinct color difference (ΔE* = 2.01) between the two varieties of confiture. Despite the heat treatment and the addition of sucrose in the BC and the EC made from Romanian fruits, wild flora can still be considered to be a valuable source of phytonutrients. The values of the primary quality indicators of the wild elderberry confiture are very similar to those of the variety made from Romanian bilberries.